2016
DOI: 10.3389/fpsyg.2016.00988
|View full text |Cite
|
Sign up to set email alerts
|

Children with Attention Deficit/Hyperactivity Disorder and Reading Disability: A Review of the Efficacy of Medication Treatments

Abstract: Reading is a multifaceted skillset that has the potential to profoundly impact a child’s academic performance and achievement. Mastery of reading skills is often an area of difficulty for children during their academic journey, particularly for children with Attention Deficit/Hyperactivity Disorder (ADHD), Specific Learning Disorder with Impairment in Reading (SLD-R), or children with a comorbid diagnosis of both ADHD and SLD-R. ADHD is characterized by executive functioning and impulse control deficits, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 39 publications
2
12
0
3
Order By: Relevance
“…The three independent disorders model would imply that treating children with interventions developed for the single disorders may be suboptimal, which could explain why COM children do not benefit from single‐disorder therapies as much as their peers who suffer from RD or ADHD alone (Bental & Tirosh, ; Pritchard, Nigro, Jacobson, & Mahone, ; Rabiner, Malone, & Conduct Problems Prevention Research Group, ; Sexton et al, ). For a comprehensive review about clinical interventions for COM, see Gray and Climie ().…”
Section: Resultsmentioning
confidence: 99%
“…The three independent disorders model would imply that treating children with interventions developed for the single disorders may be suboptimal, which could explain why COM children do not benefit from single‐disorder therapies as much as their peers who suffer from RD or ADHD alone (Bental & Tirosh, ; Pritchard, Nigro, Jacobson, & Mahone, ; Rabiner, Malone, & Conduct Problems Prevention Research Group, ; Sexton et al, ). For a comprehensive review about clinical interventions for COM, see Gray and Climie ().…”
Section: Resultsmentioning
confidence: 99%
“…The great majority of these studies examined RD with comorbid ADHD. Results from these studies are summarized in recent reviews ( 56 , 116 ). In summary, these studies have investigated the use of atomoxetine (ATX), methylphenidate (MPH), and nutritional supplements such as polyunsaturated fatty acids ( 117 ) on outcomes of reading, ADHD symptoms, and executive functions in ADHD + RD groups.…”
Section: Treatmentmentioning
confidence: 99%
“…In summary, these studies have investigated the use of atomoxetine (ATX), methylphenidate (MPH), and nutritional supplements such as polyunsaturated fatty acids ( 117 ) on outcomes of reading, ADHD symptoms, and executive functions in ADHD + RD groups. Reviews reporting on treatment studies found that outcome effect sizes range from small to medium [as low as 0.13 for ATX and as high as 0.60 for MPH ( 56 )], although effects on ADHD symptoms are larger and more consistent than for executive function or reading ( 56 , 116 ). Future work in this area should investigate the impact of these and other medications on RD with other commonly co-occurring conditions, as well as examine the neurophysiological mechanisms of these treatments in comorbid groups.…”
Section: Treatmentmentioning
confidence: 99%
“…However, all of the long‐term studies in uncomplicated ADHD samples are limited by their lack of control for some important potential confounding variables. Unlike MPH, there has been little prior study of either short‐term or long‐term atomoxetine effects on standardized academic achievement test outcomes in uncomplicated ADHD samples, so it is not possible to provide further contextualization of the findings in ADHD + RD samples.…”
Section: Medication Effects On Academic Outcomes In Adhd + Rd Vs Adhmentioning
confidence: 99%